How to Motivate the Employees in Taiwanese Multinational Corporations Operating in Vietnam - Dan, Nguyen Thi Thanh (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2016)
Abstract The study draws on recently gathered data about 210 employees of seven Taiwanese enterprises operating in the Northern Vietnam, includingHanoi, Bac Ninh and Thai Binh provinces. The data was analyzed using mean item score and Spear correlation matrix. The analysis results show that: (1) The average score of human resources index is about 3.4527, in which relationships, organizational effectiveness and organizational objectives factors are highest; (2) The top five motivating factors with highest satisfaction are included work safety, interpersonal relationships, social aspect of important work, helping others work, and social security; (3) There is a significant positive correlation between insensitive satisfaction and human resources index. Based on these analysis results, this study proposes some solutions to improve human resource management in Taiwanese multinational corporations operating inVietnam. Received 17 May 2016, revised 9 June 2016, accepted 28 June 2016 Keywords: Motivation, Taiwanese multinational corporations, Vietnam, human resources index, satisfaction.